Perbandingan Volume Kebutuhan Baja pada Pembuatan Struktur Rangka Atap Bentang 30 m Berdasarkan SNI 1729-2015 - Anggraini, Sella; Bayzoni, Bayzoni; Husni, Hasti Riakara (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2017)
The use of steel as a framework for the roof of the warehouse building requires research on the efficiency of its volume according to the form of the frame designed by considering the strength and the economical of the building materials. In the implementation of this research the calculation of structural analysis using method of joint. The outline of the implementation step is to determine the profile data (quality and dimensions) and various controls on Gording, calculate the loading using SNI 1727-2013, calculate the structure analysis of each roof frame using Microsoft Excel, calculate the analysis of truss frame design (Tensile and press memberss), weld joint planning using SNI 1729-2015 and calculate the steel requirement volume ratio of the four types of roof truss structure. The result of the research shows that the volume of steel used in Type 1 roof truss construction is 0,2046 m3 with weight 1571,4287 kg; In Type 2 roof truss construction is 0,1862 m3 with weight 1461,5889 kg; In Type 3 roof truss construction is 0,1499 m3 with weight 1176,0578 kg; In Type 4 roof truss construction is 0,1488 m3 with weight 1167,4652 kg. Based on these results, the Type 4 is the most optimal type of roof truss construction, because the lowest volume and weight of steel was obtained. Keywords: Roof frame, SNI 1729-2015, steel, tensile member, press member